(untitled) (Socio-economic relations in the digital society, 2019)
The processes of modern social development are considered in the aspect of infl uence of the systems of production, economic and financial strategy on the social values. Proven that the modern man submits to the continuous producting and consumption, while spiritual, moral principles of human existence appear the most problematic aspect of the modern state of humanity that attained extraordinary successes in the field of scientific and technical progress and mass consumption, but is loseing the spiritual mechanisms of self-preservation.